Thermal performance improvement of microchannel heat sink for electronic device cooling system using numerical analysis - Muhammad Aidil Safwan, Abdul Aziz; Nofrizalidris, Darlis; Izuan Amin, Ishak; Nor Atiqah, Zolpakar; Mohammad Arafat, .; Muhammadu, Masin Muhammadu (Semarak Ilmu Publishing, 2024)
The increasing miniaturization of technology has intensified thermal challenges, particularly concerning the cooling of small components like integrated circuits and personal computer. In order to guarantee the safety and extended operation of these devices, the thermal performance must be looked into with the purpose of dissipating them. One of the most common solutions is a microchannel heat sink (MCHS) because of its inherent property of a higher surface area-to-volume ratio. Microchannel heat sinks offer a common solution, but optimizing their configurations remains a subject of interest especially when incorporating multiple thermal enhancing methods within a microchannel heat sink. The objectives of the study is to analyse the effects of varying pin-fin geometries on key thermal performance metrics, such as maximum temperature and pressure drop, and also observing and comparing the streamline patterns generated within the crossflow microchannel heat sink. Computational Fluid Dynamics (CFD) simulations were conducted using Ansys to evaluate the thermal performance of different pin-fin geometries and also capture the streamlines pattern generated from the studied geometry of the pin fin. The results indicate that hexagon-shaped pin-fins reduced the maximum temperature by 1 to 3 Kelvin compared to the base model with circular pin-fins. However, while the circular pin-fins produced the lowest pressure drop, the hexagon-shaped pin-fins had the second-highest pressure drop among the geometries studied. This proves the significance of geometry selection for the pin fin as it affected the thermal performance of the microchannel heat sink with cross flow effects.